A Farm Newspaper Capitulates to Advertiser Pressure: Determinants of Readers’ Attitudes toward the Firing of an Editorial Cartoonist - Lulu Rodriguez; Supathida Kulpavaropas (Journal of Applied Communications, 2018)
On April 2016, the weekly Farm News cut its ties with veteran freelancer Rick Friday who drew a cartoon that called attention to how much the CEOs of large agricultural corporations are paid. This study examines the determinants of people’s attitudes toward Mr. Friday’s firing. Using data gathered from a national online survey of newspaper readers, this study traced the antecedents of these attitudes. While the incident drew strong negative reactions, we found that public attitudes were strongly mediated by readers’ attitudes toward Big Ag advertisers. That is, those who saw Big Ag in a positive light were more inclined to report less negative attitudes toward the firing. Another factor that influenced public reaction is the way people perceived the relationship between the farm press and their large corporate advertising sponsors. These findings indicated audience awareness of the synergy between content making and profit making in the farm news business, and that readers saw the relationship between big advertisers and the press as not necessarily adversarial. Those in agricultural states tended to see the editorial cartoon and the firing incident as more relevant to their lives than their counterparts in non-agricultural areas. However, the perceived relevance of the editorial cartoon and the firing incident had no bearing on people’s attitudes toward the incident. Implications of the findings on fostering a healthy relationship between farm newspapers, their readers, and the agribusinesses that advertise in them are discussed.
Keywords: farm newspapers; Big Ag advertisers; editorial-advertising relationship; advertising pressure on editorial content; media ethics; attitudes toward Big Ag; relationship between farm newspapers and advertisers